I disegni inediti di Domenico Cirillo nella Società dei Naturalisti in Napoli - De Natale, Antonino (Cavoliniana. Monografie della Società dei Naturalisti in Napoli, 2021)
From the reorganization of the Archive of the Society of Naturalists in Naples, some drawings of insects and plants by Domenico Cirillo (1739-1799) reappear after two hundred and twenty years, fortunately escaped the fury of the Sanfedisti when they sacked and destroyed his house. They were confused among the papers of his pupil and friend Filippo Cavolini (1756-1810). Carefully studied in this volume, they are for the first time made known to scholars and admirers of the great physician and naturalist, who died for his ideals of justice and for the renewal of the old regime society. In addition to contributions documenting the contacts that Cirillo had with artists and printers, the volume also includes information on the costs he incurred for the publication of his books, to which is added the history that occurred to the manuscript papers of Filippo Cavolini and its descendants, the family De Mellis, which merged into the Society of Naturalists.